The art of peace and relaxation workbook - Seaward, Brian Luke (Jones & Bartlett Pub, 2015)
The perfect companion to Managing Stress: Principles and Strategies for Health and Well-Being, Eighth Edition, this workbook contains more than 130 stress management exercises that will show you how to withstand the pressures of whatever stress may come your way. Collectively, these surveys, questionnaires, inventories, journal entries, and worksheets are designed as a comprehensive action plan to help you develop effective coping skills and learn to use proven relaxation techniques